2017
DOI: 10.3945/ajcn.116.139626
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of nutrition therapy compared with dietary advice in patients with type 2 diabetes

Abstract: Background: Despite recommendations, many patients with type 2 diabetes receive dietary advice from nurses or doctors instead of individualized nutrition therapy (INT) that is provided by a dietitian. Objective: We performed a meta-analysis to compare the effect of INT that is provided by a registered dietitian with the effect of dietary advice that is provided by other healthcare professionals. Design: A systematic review was conducted of Cochrane library databases, EMBASE, CINAHL, and MEDLINE in the period 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 15 publications
1
48
0
2
Order By: Relevance
“…A more comprehensive dietary education program that addressed barriers such as lack of support from family and health services, time management and dietary myths [ 37 39 ] could result in an even better dietary behaviour change. A successful program could also take into consideration factors such as meal planning, diet quality, self-monitoring, dietary self-efficacy, social support and time management [ 40 43 ], and deliver it through trained professionals such as dieticians or nutritionists functioning as part of multidisciplinary teams [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more comprehensive dietary education program that addressed barriers such as lack of support from family and health services, time management and dietary myths [ 37 39 ] could result in an even better dietary behaviour change. A successful program could also take into consideration factors such as meal planning, diet quality, self-monitoring, dietary self-efficacy, social support and time management [ 40 43 ], and deliver it through trained professionals such as dieticians or nutritionists functioning as part of multidisciplinary teams [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that better clinical parameters, such as reduced hemoglobin A1c concentration, weight loss, and improved lipid profile, are achieved when the dietary intervention is led by a dietitian as opposed to any other health professional. 10 Even a single session with a dietitian improves hemoglobin A1c levels. 11 Yet, suboptimal use of dietetic services is evident worldwide, with a large proportion of people with T2DM never consulting a dietitian.…”
Section: Introductionmentioning
confidence: 99%
“…Están surgiendo pruebas de que la atención nutricional otorgada por el nutricionista se proporciona mejor y se logra un resultado superior del paciente (24)(25)(26).…”
Section: Discussionunclassified